Tent Caterpillar Epidemic in Betula Utilis Forest in Pithoragarh District of Uttar Pradesh and its Control - Bhandari, R. S.; Singh, Pratap (Indian Forester, 1991)
Epidemic defoliation of Betula utilis D. Don (Bhojpatra) was reported for the first time in Pithoragarh in 1984-85. A study was undertaken in May, 1986 to diagnose the epidemic and toggest control measures which is described in detail.